Mengasah Potensi Kepribadian Anak melalui Pendekatan Komunikasi Positif - Ahmad, Nur (THUFULA, 2015)
Positive communication is communication that is able to develop its positive potency of children. Positive communication is built to form the fabric of a child’s personality that will also be established between parents and children. It can cultivate emotional intelligence. Of course, these two things will make a valuable provision for children’s development in the future. While missed communication would cause them uneducated and ignorant. Failure in communicating wouldnormally make a child called weird or crazy. Actually there are a few tips to succeed in realizing the potency of the child’s qualified personality, such as provide exemplary son, make the house as a science park, provides a vehicle for creativity, avoid negative emotions and always pray for children to be always given a good personality and mental health. Later in the development potency of the child’s personality can also be affected by a variety of factors. One of them is the positive communication patterns of parents towards their children (get them to always communicate in a positive environment). If the communication patterns of parents are bad, the negative impact will be felt by the child as well.